Doroczny bieg uliczny o puchar "Głosu Wybrzeża". (Gdańsk : [s.n.], 1950)
Afisz z inf. o biegach, które miały miejsce 6.05.1950 r.
Keywords: Sport -- Polska -- Gdynia -- 1945-1970 -- druki ulotne; Sport -- Polska -- Gdynia -- 1945-1970 -- plakaty; Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- plakaty; Gdańsk (Polska) -- 1945-1970 -- źródła